Study Of Devulcanized Natural Rubber as The Green Impact Modifier for Polypropylene With Electron Beam Irradiation - Loo, Kheng Hooi (2018)
The effects of DVC composition, EB irradiation and UV source degradation in relation to the performance of the PP DVC compound were investigated. Various DVC compositions (0 phr 20 phr) were compounded with PP and irradiated at several dosages (0 kGy 200 kGy) und er natura l weathering condition (0 month 6 months). It was found that with the addition of 5 phr DVC added in PP irradiated at 50 kGy has the optimum value of the mechanical properties after 6 months outdoor exposure. It could provide better tensile stre ngth, impact strength and hardness value as the DVC particles dispersed better in PP matrix. The gel content increased with longer exposure period due to a more extensive three dimensional network formation via a substantial reaction with the larger amount of free radicals promotes at low irradiation dosages. There is an expansion of crystallize size caused by the photo oxidation where the chain arrangement around crystalline structure reorientated However, the intensity of the peaks and crystallinity reduced after outdoor exposure due to the photo oxidation occurs has broken down the crystalline structure in the PP matrix . Furthermore, the fractured surface has changed from tear lines appearance to flake like appearance because of the UV exposure has caused the polymer degradation and reduced the filler matrix interaction. Furthermore, the appearance of two new peaks at 1710 cm 1 and 3300 cm 1 which are C=O stretching vibrati on and O H stretching vi bration indicated that the photo oxidation and electron beam irradiation occurs.